The Model of Management of Scientific Magazines as an Information Technology Based Learning Media at the Madrasah Aliyah Library in Malang - Sokhibul Ansor; Punaji Setyosari; I Nyoman Sudana Degeng; Waras Waras (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
The magazine management model is a new product in managing scientific magazines that can be applied in all Madrasah Aliyah in Indonesia with manual based and will be developed again based on automation. This study begins with a preliminary study through a survey which shows that the scholarly magazines that were subscribed or derived from the prizes at the Madrasah and Aliyah libraries have not been processed with standards. The research design used is a development method that aims to make an effective product and not test a theory. In the first phase, exploration of scientific magazine management data will be conducted at Madrasah Aliyah Library in Malang and the drafting of guidelines for the model of scientific magazine management model which will produce the draft model of scientific magazine management in Madrasah Aliyah Library Malang Raya The results of research in the first phase of the first year is made a model of scientific magazine management based on information technology that includes: inventory of magazines, catalogs of scientific magazines, magazine scientific index, scientific magazine holding list model the management of science-based scientific magazines by modifying the open source SLIM Akasia software. In the second phase of the second year will be attempted installation of the latest installation of the results of research on libraries Madrasah Aliyah East Java.